The Phonological Enterprise. - Hale, Mark (OUP Oxford, 2008)
Mark Hale and Charles Reiss present a fundamental critique of the phonological enterprise. They examine the nature of phonological acquisition and its relation to an innate acquisition device, consider the distinction between competence and performance, and evaluate competing explanations of diachronic phonology. - ;This book scrutinizes recent work in phonological theory from the perspective of Chomskyan generative linguistics and argues that progress in the field depends on taking seriously the idea that phonology is best studied as a mental computational system derived from an innate base.